Storytelling, citra destinasi, dan pengalaman merek pada video promosi kementerian pariwisata dan ekonomi kreatif - Wahyu, Anabel Yevina Mulyadi; Berto, Agustinus Rusdianto; Murwani, Endah (Jurnal Studi Komunikasi, 2022)
The Ministry of Tourism and Creative Economy (Kemenparekraf) of the Republic of Indonesia is aggressively promoting tourist destinations with various policies after confirmed cases of Covid-19 decreased. Efforts to promote tourist destinations are created a positive image of Indonesian tourism destinations. The promotional video used storytelling techniques from Bali and Lake Toba, two Indonesian tourist destinations. This study aimed to determine the effect of the Ministry of Tourism and Creative Economy's tourism promotion videos using storytelling techniques on the image of the destination, mediated by brand experience. This study uses a quantitative approach with experimental research methods. The results of this study indicate that the storytelling in The Heart Beat of Toba (53.4%) and Earth Revitalisation (22.5%) videos influences the image of the destination mediated by brand experience.